Biomaterials approaches to modeling macrophage–extracellular matrix interactions in the tumor microenvironment. (August 2016) - Springer, Nora L; Fischbach, Claudia
Graphical abstract: Highlights: Macrophagic inflammation and fibrosis synergistically prime the microenvironment for cancer. Fibrosis changes ECM physicochemical properties, which alters macrophage mechanosignaling. Biomaterials can mimic fibrosis-associated differences in ECM physicochemical properties. Tissue-engineered models permit testing the role of fibrosis in macrophage functions. Abstract : Tumors are characterized by aberrant extracellular matrix (ECM) remodeling and chronic inflammation. While advances in biomaterials and tissue engineering strategies have led to important new insights regarding the role of ECM composition, structure, and mechanical properties in cancer in general, the functional link between these parameters and macrophage phenotype is poorly understood. Nevertheless, increasing experimental evidence suggests that macrophage behavior is similarly controlled by physicochemical properties of the ECM and consequential changes in mechanosignaling. Here, we will summarize the current knowledge of macrophage biology and ECM-mediated differences in mechanotransduction and discuss future opportunities of biomaterials and tissue engineering platforms to interrogate the functional relationship between these parameters and their relevance to cancer.